Patent Foramen Ovale in Cryptogenic Ischemic Stroke: Direct Cause, Risk Factor, or Incidental Finding? - Ioannidis, Stefanos G.; Mitsias, Panayiotis D. (Frontiers in Neurology, 2020)
Patent foramen ovale (PFO) has been associated with cryptogenic stroke. There is conflicting data and it remains uncertain whether PFO is the direct cause, a risk factor or an incidental finding. Potential stroke mechanisms include paradoxical embolism from a venous clot which traverses the PFO, in situ clot formation within the PFO, and atrial arrhythmias due to electrical signaling disruption. Main risk factors linked with PFO-attributable strokes are young age, PFO size, right-to-left shunt degree, PFO morphology, presence of atrial septal aneurysm, intrinsic coagulation-anticoagulation systems imbalance, and co-existence of other atrial abnormalities, such as right atrial septal pouch, Eustachian valve and Chiari's network. These may act independently or synergistically, multiplying the risk of embolic events. The RoPE score, a scale that includes factors such as young age, cortical infarct location and absence of traditional stroke risk factors, is associated with the probability of a PFO being pathogenic and stroke recurrence risk after the index stroke. Multiple investigators have attempted to correlate other PFO features with the risk of PFO-related stroke, but further investigation is needed before any robust conclusions are reached. PFO presence in young patients with cryptogenic stroke should be considered as etiologically suspect. Caution should be exercised in interpreting the relevance of other PFO features.